Effect Of Secondary Plastic Deformation On The Microstructures And Mechanical Properties Of Cast Ai-7Si-Mg Alloy - Thuong, Nguyen Van (2014)
The purpose ofthis research is to study microstructure and hardness of AI-7SiMg alloy under different cooling slope casting conditions and equal channel angular pressing (ECAP). The effect of cooling slope casting method with varying variables, such as pouring temperature (625°C - 640°C - 660°C - 680°C), cooling slope length (150 mm - 250 mru- 350 mm) and cooling slope temperature (room temperature - 200°C - 400°C) and conventional casting method are investigated. The as-cast alloys and as-ECAPed alloys were analyzed based on Differential Scanning Calorimetry, Xray fluorescence, microstructures, hardness, X-ray Diffraction pattern, wear resistance, Secondary Electron Microscope and Energy Dispersive X-ray. Microstructure of conventional cast alloy cast at pouring temperature of 640°C was coarse and almost dendrite the structure. However, uniform, fine and globular microstructure could be obtained from cooling slope casting with pouring temperature range of 625°C - 660°C, cooling slope length range of 150 mm - 350 mm and slope temperature ranging from room temperature to 200°C_ This is due to copious nucleation occurred on slope surface and these nuclei were then detached due to the force convection during pouring process.